Palladium‐Catalyzed Desulfitative Cross‐Coupling of Sodium Arylsulfinates with Aryl Bromides and Chlorides: An Alternative Convenient Synthesis of Biaryls. Issue 10 (17th October 2013) - Zhou, Chao; Li, Yaming; Lu, Yang; Zhang, Rong; Jin, Kun; Fu, Xinmei; Duan, Chunying
Abstract An alternative method for synthesis of biaryls has been developed through the Pd catalyzed desulfitative coupling reaction of sodium arylsulfinates with aryl bromides and chlorides. The procedure tolerates a variety of functional groups, such as cyano, formyl, acetyl, chloro, methoxy, trifluoromethyl and heteroaromatic unit. The desired products were obtained in moderate to excellent yields under relatively mild reaction conditions without additives, base or co‐catalyst.